Receipt of Pharmacotherapy for Alcohol Use Disorder by Male Justice-Involved U.S. Veterans Health Administration Patients. (December 2018) - Finlay, Andrea K.; Binswanger, Ingrid; Timko, Christine; Rosenthal, Joel; Clark, Sean; Blue-Howells, Jessica; McGuire, Jim; Hagedorn, Hildi; Wong, Jessie; Van Campen, James; Harris, Alex H. S.
This study examined whether, among Veterans Health Administration (VHA) patients, veterans with recent or current justice involvement have equal receipt of pharmacotherapy for alcohol use disorder compared with veterans with no justice involvement. Using national VHA records, we calculated the overall and facility rates of receipt as the number of patients who received pharmacotherapy for alcohol use disorder divided by the number of patients diagnosed with an alcohol use disorder. Using a mixed-effects logistic regression model, we tested whether justice involvement was associated with pharmacotherapy receipt. Male veterans with jail/court involvement had significantly higher odds of receiving pharmacotherapy for alcohol use disorder compared with other male veterans. Justice-involved veterans had equal or better receipt of pharmacotherapy for alcohol use disorder compared with veterans with no justice involvement. Pharmacotherapy rates are low overall, suggesting that more work can be done to connect veterans to these medications.